Periodic laminar flow and heat transfer in a channel with 45° staggered V-baffles - Promvonge, Pongjet; Kwankaomeng, Sutapat (My University, 2010)
A numerical investigation has been carried out to examine periodic laminar flow and heat transfer characteristics in a three-dimensional isothermal wall channel of aspect ratio, AR=2 with 45° staggered V-baffles. The computations are based on the finite volume method, and the SIMPLE algorithm has been implemented. The fluid flow and heat transfer characteristics are presented for Reynolds numbers based on the hydraulic diameter of the channel ranging from 100 to 1200. To generate two pair of main streamwise vortex flows through the tested section, V-baffles with an attack angle of 45° are mounted in tandem and staggered arrangement on the lower and upper walls of the channel. Effects of different baffle heights on heat transfer and pressure drop in the channel are studied and the results of the V-baffle pointing upstream are also compared with those of the V-baffle pointing downstream. It is apparent that in each of the main vortex flows, a pair of streamwise twisted vortex (P-vortex) flows can induce impinging flows on a sidewall and a wall of the interbaffle cavity leading to drastic increase in heat transfer rate over the channel. In addition, the rise in the V-baffle height results in the increase in the Nusselt number and friction factor values. The computational results reveal that the optimum thermal enhancement factor is around 2.6 at baffle height of 0.15. times of the channel height for the V-baffle pointing upstream while is about 2.75 at baffle height of 0.2. times for the V-baffle pointing downstream. © 2010 Elsevier Ltd.
Keywords: Channel; Heat transfer; Laminar flow; Periodic flow; V-baffle